Corrigendum to "Global frequency and intensity analysis of the ν10/ν7/ν4/ν12 band system of 12C2H4 at 10 μm using the D2 h top data system" [J. Quant. Spectrosc. Radiat. Transf. 182 (2016) 158–171]. (March 2017) - Alkadrou, A.; Bourgeois, M.-T.; Rotger, M.; Boudon, V.; Vander Auwera, J.
Abstract: This corrigendum provides a new version of one of the 3 supplementary data files associated with the article A. Alkadrou et al., J. Quant. Spectrosc. Radiat. Transf. 182 (2016) 158–171, namely the HITRAN-formatted linelist generated as described in section 5 of the article. Indeed, the K a and K c labels of the upper levels of a number of transitions belonging to the ν 10, ν 7 and ν 4 bands listed in this supplementary data file were found to be incorrect. The linelist provided with this corrigendum corrects these erroneous assignments, and provides K a and K c labels for all the upper levels.